The therapeutic effects of bone marrow mesenchymal stem cells after optic nerve damage in the adult rat - Tan HB (Dove Medical Press, 2015)
HaiBo Tan,1,* Xin Kang,2,* ShiHeng Lu,1 Lin Liu1 1Department of Ophthalmology, RenJi Hospital, The School of Medicine, Shanghai JiaoTong University, Shanghai, People’s Republic of China; 2Department of Clinical Pharmacology, Changhai Hospital Affiliated Second Military Medical University, Shanghai, People’s Republic of China *These authors contributed equally to this work Abstract: Optic nerve trauma is a common occurrence that results in irreversible blindness. Currently, no effective strategies are known to prevent optic nerve degeneration. We assessed the therapeutic effects of bone marrow mesenchymal stem cells (BMSCs) after optic nerve crush in the adult rat. Our results showed that BMSCs significantly promoted the regeneration of injured axons compared with phosphate buffered saline alone. Therefore, BMSC transplantation may be effective for the treatment of central nervous system disorders. Keywords: bone marrow mesenchymal stem cell, axonal regeneration, rat optic nerve crush, nervous system disorders